Effect of heat transfer conditions on the ignition characteristics of dispersed solid fuel; Russian Journal of Physical Chemistry B; Vol. 9, iss. 6 - Zakharevich A. V. Arkadiy Vladimirovich (Combustion, Explosion, And Shock Waves, 2015)
Title screen